PELATIHAN TEKNIS PENANAMAN PADI BAGI PENYULUH PERTANIAN - Mulono Apriyanto; Nursida; Hermiza Mardesci; Marlina; Yeni Afiza; Retty Ninsix; Yoyon Riono; Rifni Novitasari; Partini; Yulianti (Bajang Institute, 2021)
Extension is a partnership between government, landowners and communities, providing planned care and education to meet community needs. The purpose of community service is to increase the ability of extension workers in the technique of jajar legowo rice cultivation. The training method is the presentation of material and practice. The results of community service show an increase in the ability of extension workers in the technique of planting jajar legowo rice.